Integration Performance Management and ISO 9001:2015 Implementation - Suyanto, Mike; Sary, Fetty Poerwita (Side: Scientific Development Journal, 2025)
Many companies in Indonesia have adopted ISO 9001:2015 ( Quality Management System) but have not yet achieved the expected performance levels . The research aiming to assist companies in enhancing performance and Integration the implementation of Performance Management with the existing ISO 9001:2015 quality management system . The major phenomenon in this research is the declining company's performance despite implementing ISO 9001:2015. This research aiming to help companies develop a Performance Management system aligned with their business processes and corporate strategy . This research adopt a qualitative approach approach to data gathering and information through document observation and FGD interviews . The researcher found that companies have not had a system to deploy the company's strategy to all levels and how to measure it . The researcher also suggests that the company establish the integration model for implementing the 6.2, 7, 9, and 10 clauses of ISO 9001:2015. The integration with ISO 9001:2015 should be implemented for Sustainability Performance Management.